2016
DOI: 10.1111/jth.13244
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological concentrations of recombinant factor VIIa restore hemostasis independent of tissue factor in antibody‐induced hemophilia mice

Abstract: Summary Background Recombinant factor VIIa (rFVIIa) has been used widely for treating hemophilia patients with inhibitory autoantibodies against factor VIII or IX. Its mechanism of action is not entirely known. A majority of in vitro studies suggested that pharmacological concentrations of rFVIIa restore hemostasis in hemophilia in a phospholipid-dependent mechanism, independent of tissue factor (TF). However, a few studies suggested that a TF-dependent mechanism plays a primary role in rFVIIa correction of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…Finally, FVIIa mode of action studies using TGA should be performed with caution; in sharp contrast to our TGA finding, the relatively poor factor X–activating ability of FVIIa in solution leaves little doubt in our minds that phospholipid association is utterly important for the pharmacologic effect of FVIIa, and neither does the documented effect of FVIIa on platelet adhesion and activation under flow conditions . Recent data strongly supporting a TF‐independent mode of action of FVIIa, neither competing with zymogen for TF nor requiring TF for its own effect, support the necessity of a direct interaction with procoagulant membrane surfaces …”
Section: Resultscontrasting
confidence: 59%
“…Finally, FVIIa mode of action studies using TGA should be performed with caution; in sharp contrast to our TGA finding, the relatively poor factor X–activating ability of FVIIa in solution leaves little doubt in our minds that phospholipid association is utterly important for the pharmacologic effect of FVIIa, and neither does the documented effect of FVIIa on platelet adhesion and activation under flow conditions . Recent data strongly supporting a TF‐independent mode of action of FVIIa, neither competing with zymogen for TF nor requiring TF for its own effect, support the necessity of a direct interaction with procoagulant membrane surfaces …”
Section: Resultscontrasting
confidence: 59%
“…FVIIa AI , which binds TF with very high affinity, 15 could effectively block TF-FVIIa complex formation and thus inhibits TF-dependent thrombus formation. Studies from our laboratory 13 and others 30 showed that the hemostatic effect of rFVIIa in hemophilia stems from the TF-independent mechanism. FVIIa binding to phospholipids exposed on the activated platelets and the platelet-bound FVIIa activation of FX are thought to be responsible for the hemostatic effect of rFVIIa in hemophilia patients.…”
Section: Discussionmentioning
confidence: 93%
“…13 Briefly, bleeding was induced by a sharp incision to the saphenous vein, and the bleeding from the cut was monitored for 30 min. After each hemostasis incident, the clot was disrupted gently to reinitiate a new bleeding episode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Thus, inhibition of TFPI with concizumab extends FX activation within the initiation phase of coagulation and protects the prothrombinase complex at the platelet surface. 6,7 In the present study, the effect of concizumab and rFVIIa on blood loss in a cuticle bleeding model in haemophilic rabbits was compared when the compounds were administered at different time points after bleeding induction. 3,4 Concizumab exhibits cross-reactivity with rabbit TFPI and reduced bleeding dose-dependently in haemophilic rabbits after intravenous or subcutaneous administration prior to and up to 5 minutes after bleeding initiation.…”
Section: Concizumab Promotes Haemostasis Via a Tissue Factor-factormentioning
confidence: 99%